Therapeutic efficacy of dihydroartemisinin-piperaquine combination for the treatment of uncomplicated malaria in Ghana - Abuaku, Benjamin; Boateng, Paul; Peprah, Nana Yaw; Asamoah, Alexander; Duah-Quashie, Nancy Odurowah; Matrevi, Sena Adzoa; Amoako, Eunice Obeng; Quashie, Neils; Owusu-Antwi, Felicia; Malm, Keziah Laurencia; Koram, Kwadwo Ansah (Frontiers in Cellular and Infection Microbiology, 2023)
In 2020, Dihydroartemisinin-Piperaquine (DHAP) was adopted as a second-line antimalarial for treatment of uncomplicated malaria in Ghana following a review of the country’s antimalarial medicines policy. Available data obtained in 2007 had shown PCR-uncorrected therapeutic efficacy of 93.3% using a 28-day follow-up schedule. In 2020, the standard 42-day follow-up schedule for DHAP was used to estimate efficacy levels among febrile children aged 6 months to 9 years in three malaria sentinel sites representing the three main ecological zones of the country- savannah, forest, and coastal. PCR genotyping distinguished between recrudescence and re-infection using merozoite surface protein 2 (MSP2)-specific primers for FC27 and 3D7 strains. Per protocol analyses showed day 28 efficacy of 100% in all three sentinel sites with day 42 PCR-corrected efficacy ranging between 90.3% (95% CI: 80.1 – 96.4%) in the savannah zone and 100% in the forest and coastal zones, yielding a national average of 97.0% (95% CI: 93.4 – 98.8). No day 3 parasitemia was observed in all three sites. Prevalence of measured fever (axillary temperature ≥ 37.5°C) declined from 50.0 - 98.8% on day 0 to 7.1-11.5% on day 1 whilst parasitemia declined from 100% on day 0 to 1.2 - 2.3% on day 1. Mean haemoglobin levels on days 28 and 42 were significantly higher than pre-treatment levels in all three sites. We conclude that DHAP is highly efficacious in the treatment of uncomplicated malaria in Ghana. This data will serve as baseline for subsequent DHAP efficacy studies in the country.